NORMS FOR ULTIMATE BENDING MOMENTS OF SOME MAIN TYPES OF GLUED CORNER JOINTS OF STRUCTURAL ELEMENTS OF ONE-LAYER PINE WOOD BOARDS - Marinova, Assia (Innovation in Woodworking Industry and Engineering design, 2012)
The main factors concerning the strength and shape stability of the case furniture are the strength and stiffness of the joints between the furniture‟s structural elements. Presently, there is high interest in furniture made of solid wood boards. This requires new studies for evaluating the strength and stiffness characteristics of corner joints of structural elements made of solid wood boards.In this study the data are given about the experimentally established ultimate bending moments of some of the most frequently used glued corner joints of structural elements made of one-layer solid pine wood boards under compression bending test. On this basis norms for ultimate bending moments are propounded.It was established that the type of the joints has a significant influence on their strength under bending loading. The determined ultimate bending moments and their normative values of the tested glued corner joints of one-layer solid wood boards of Scots pine under bending loading can be used by furniture designers in strength investigations of solid wood furniture, as well as for the quality assurance control in manufacturing.